Screening and reverse transcription quantitative PCR based validation of resistance to tobacco streak virus (TSV) in sunflower germplasm: PCR BASED VALIDATION OF RESISTANCE TO TSV IN SUNFLOWER GERMPLASM - B PARAMESWARI; G V CHAITRA; BHASKAR BAJARU; L SARAVANAN; D RAMESH; V CELIA CHALAM (Journal of Oilseeds Research, 2026)
Sunflower necrosis disease (SND), incited by tobacco streak virus (Ilarvirus TSV), poses a serious threat to sunflower production causes substantial yield losses. The present investigation aimed to identify and validate the sources of resistance in sunflower germplasm through integrated phenotypic screening and reverse transcription quantitative PCR (RT-qPCR)-based viral titre estimation. A total of hundred exotic accessions, along with five susceptible checks, were evaluated under field and controlled glasshouse condition across multiple cropping seasons. Initial classification based on percent disease incidence and severity indicated a wide spectrum of responses, including immune and resistant lines. However, absolute quantification using RT-qPCR, employing a plasmid-derived standard curve (R²=0.9866; slope=-3.2171), revealed the absence of true immunity, as all accessions exhibited detectable TSV titres. Resistant accessions (EC1119718, EC1119731, EC1119737, EC1119750, EC1119780, EC1119785, EC1119880, EC1119884) consistently maintained low viral loads (3.4 × 10³ to 7.1 × 10³), indicating restricted viral replication and systemic movement. The study highlights the limited reliability of symptom-based phenotyping for resistance determination, as asymptomatic or low-symptom germplasm may harbour high viral titres. The identified resistant germplasm constitutes a valuable genetic resource for TSV resistance breeding, emphasizing the necessity of integrating molecular diagnostics with conventional screening for effective selection strategies.